Identification of Novel FBN2 Variants in a Cohort of Congenital Contractural Arachnodactyly - Sun, Liying; Huang, Yingzhao; Zhao, Sen; Zhong, Wenyao; Shi, Jile; Guo, Yang; Zhao, Junhui; Xiong, Ge; Yin, Yuehan; Chen, Zefu; Zhang, Nan; Zhao, Zongxuan; et al. (Frontiers in Genetics, 2022)
Congenital contractural arachnodactyly (CCA) is a rare autosomal dominant disorder of connective tissue characterized by crumpled ears, arachnodactyly, camptodactyly, large joint contracture, and kyphoscoliosis. The nature course of CCA has not been well-described. We aim to decipher the genetic and phenotypic spectrum of CCA. Method: The cohort was enrolled in Beijing Jishuitan Hospital and Peking Union Medical College Hospital, Beijing, China, based on Deciphering Disorders Involving Scoliosis and COmorbidities (DISCO) study (http://www.discostudy.org/). Exome sequencing was performed on patients’ blood DNA. A recent published CCA scoring system was calculated in our cohort. Eight novel variants and two previously reported FBN2 variants through exome sequencing. Two variants outside of the neonatal region of FBN2 gene were found. The phenotypes were comparable between patients in our cohort and previous literature, with arachnodactyly, camptodactyly and large joints contractures found in almost all patients. All patients eligible for analysis were successfully classified into likely CCA based on the CCA scoring system. Furthermore, we found a double disease-causing heterozygous variant of FBN2 and ANKRD11 in a patient with blended phenotypes consisting of CCA and KBG syndrome. The identification of eight novel variants broadens the mutational and phenotypic spectrum of CCA and may provide implications for genetic counseling and clinical management.